Baseline assessment of microplastics pollution in beach sediments along tropical coastline (Kuala Langat, Malaysia) - Praveena, Sarva Mangala; Ahmad Pakharuddin, Nuremilia Affarina; Nafisyah, Ayu Lana; Karuppannan, Subramaniam; Sundaramanickam, Arumugam (Elsevier Ltd, 2025)
This study examines the occurrence, physical characteristics (size, colour, and shape), and polymer compositions of microplastics (MPs) in beach sediments along the Kuala Langat coastline impacted by tourism and fishing activities. Microplastics particle were isolated using density separation, characterized using microscopy and Spectroscopy technique. Microplastic concentrations ranged from 0.01 to 0.21 particles/g in tourist sites and 0.01 to 0.03 particles/g in non-tourist sites, indicating significantly higher MP pollution in tourism-affected areas. The longest MP particle (4951.5 μm) was found in a non-tourist area, while the shortest (84.7 μm) was detected on a tourist beach. Fragment-shaped MPs (82.40 %) were the most dominant, exhibiting a variety of colors and diverse plastic sources. Polypropylene, polyethylene, and polystyrene comprised 80 % of the detected polymers, suggesting that single-use plastics contribute substantially to MP pollution in both sampling sites. These findings provide critical insights for targeted strategies for plastic waste management in tropical coastal areas.